2020
DOI: 10.3389/fpls.2020.01210
|View full text |Cite
|
Sign up to set email alerts
|

Arabinoxylan-Oligosaccharides Act as Damage Associated Molecular Patterns in Plants Regulating Disease Resistance

Abstract: Immune responses in plants can be triggered by damage/microbe-associated molecular patterns (DAMPs/MAMPs) upon recognition by plant pattern recognition receptors (PRRs). DAMPs are signaling molecules synthesized by plants or released from host cellular structures (e.g., plant cell walls) upon pathogen infection or wounding. Despite the hypothesized important role of plant cell wall-derived DAMPs in plant-pathogen interactions, a very limited number of these DAMPs are well characterized. Recent work demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 89 publications
(129 reference statements)
5
68
0
2
Order By: Relevance
“…The pentasaccharide XA3XX triggers an oxidative burst, a rapid calcium influx, the phosphorylation of MPK3 and MPK6, and the upregulation of genes involved in innate immunity, including several PTI marker genes (CYP81F2, WRKY53, PHI1, FRK1, and NHL10). Moreover, tomato plants treated with XA3XX are more resistant to P. syringae pv tomato DC3000, and XA3XX-treated pepper plants are more resistant to Sclerotinia sclerotiorum (Mélida et al, 2020).…”
Section: Arabinoxylansmentioning
confidence: 99%
See 2 more Smart Citations
“…The pentasaccharide XA3XX triggers an oxidative burst, a rapid calcium influx, the phosphorylation of MPK3 and MPK6, and the upregulation of genes involved in innate immunity, including several PTI marker genes (CYP81F2, WRKY53, PHI1, FRK1, and NHL10). Moreover, tomato plants treated with XA3XX are more resistant to P. syringae pv tomato DC3000, and XA3XX-treated pepper plants are more resistant to Sclerotinia sclerotiorum (Mélida et al, 2020).…”
Section: Arabinoxylansmentioning
confidence: 99%
“…Arabinoxylan (AX), another hemicellulose present in both the primary and secondary walls, consists of copolymers of two pentoses: arabinose and xylose. Very recently, by analyzing mutants in Arabidopsis Response Regulators (ARRs), which mediate cytokinin signaling and modulate the disease resistance (Bacete and Hamann, 2020), it was demonstrated that the AX-derived pentasaccharide 3 3 -α-L-arabinofuranosylxylotetraose (XA3XX) triggers a strong immune response in Arabidopsis and enhances disease resistance of some crop plants (Mélida et al, 2020).…”
Section: Dynamics Of the Cell Wall And Release Of Regulatory Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fructans, polysaccharides mainly consisting of 5-membered fructose (Fru) rings, specifically inulin from plant origin, like those derived from chicory (Cichorium intybus) and burdock (Arctium lappa), are able to induce resistance against B. cinerea in lettuce [19]. Recently, xylo-oligosaccharides with 5-membered arabinose side branches were shown to act as DAMPs and elicit immune responses in plants [20]. Hitherto, β-aminobutyric acid (BABA), chitosan and OGs are among the most popular environmentally friendly agents to induce disease resistance in the agronomical context, next to the widespread use of biological control organisms and their culture filtrates (e.g., Trichoderma sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of CWI can initiate the release of DAMPs that regulate plant immune responses in a similar way to those triggered by microbe-associated molecular patterns (MAMPs) ( 6 , 24 , 47 ). Despite the diversity of glycan structures of plant cell walls, only a limited number of wall-associated DAMPs have been identified so far, including some oligosaccharides structures derived from β-1,3-glucan (callose), cellulose, xyloglucan, mannan, homogalacturonan, and arabinoxylan polysaccharides of plant cell walls ( 6 , 8 10 , 12 , 47 51 ). Modification of CWI also leads to developmental phenotype alterations (e.g., reduced plant size and biomass or fertility), indicating that the cell wall contributes to plant fitness ( 5 , 19 , 52 , 53 ).…”
mentioning
confidence: 99%